I know there's a formula somewhere, but how do you factor an equation with an exponent of three.
In my solution's manual it says: x^3 - x^2 + 11x - 6 = (x-1)(x-2)(x-3)
And i'm just trying to figure out how they got that.
I have a "Solve the initial value problem" It is:
y'' + y = 2cosx - 3sinx
I know how to do everything except for get yp. I know it has to be something so when i substitute yp into the left hand side of the equation, i get the right hand side, 2cosx - 3sinx.
By this definition i would...
I'm trying to understand this concept. Jere's the problem i'm doing.
I have to find the general solution for:
y'' + 36y = -4xsin(6x)
So you then solve for your characteristic equation and get lamda = +/- 6
so y1 = e^-6x and y2 = e^6x
You get your matrix for w, w1, and w2.